Studi Filsafat Islam : Sebuah Pendekatan Konseptual - Ahmad Ardiyansyah; Mahfud (Journal Khafi : Journal Of Islamic Studies, 2025)
This study aims to explore the nature of philosophy through a conceptual approach that emphasizes a deep understanding of the ideas, basic concepts, and methodologies used in the study of philosophy. Through a qualitative-descriptive literature review, this study analyzes the definition of philosophy, its objects of study, and the main branches that form the framework of philosophical thinking. In addition, the relevance of philosophy in contemporary life and its contribution to developing critical reasoning, ethics, and a reflective worldview are also discussed. The results of the study show that a conceptual approach in the study of philosophy provides a strong foundation for understanding the dynamics of human thought across eras and civilizations. Thus, this approach not only enriches theoretical insights but also encourages intellectual awareness in facing existential and social problems.